Making metaphor studies less WEIRD. The methodological benefits and challenges of a greater diversity of languages and cultures in the study of metaphor - Simon Devylder (Lexis: Journal in English Lexicology)
European languages represent 3% of the world 7,000+ languages, and yet, a recent survey shows that they amount for 84% of the studies in metaphor publications. The disproportionate reliance on such an infinitely small sample of the world diversity of languages seriously undermines the representativeness of generalizations about a phenomenon that is claimed to be found across languages and cultures. This paper is a call for more diversity in metaphor studies and a discussion about the methodological benefits and challenges posed by such ambition. Particularly relevant to increasing diversity in metaphor studies is the role of culture and context in metaphor identification procedures. This methodological question is addressed with a specific case study that shows how providing annotators with cultural and contextual information are key to increasing inter-rater agreements.